2001
DOI: 10.1111/j.1525-1497.2001.01111.x
|View full text |Cite
|
Sign up to set email alerts
|

Productivity, quality, and patient satisfaction

Abstract: In these academic primary care practices, rates of patient satisfaction, compliance with screening guidelines, and resource utilization were similar for part-time PCPs compared to full-time PCPs. Productivity per clinical hour was markedly higher for part-time PCPs. Despite study limitations, these data suggest that academic part-time PCPs are at least as efficient as full-time PCPs and that the quality of their work is similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Definitions of the variables are provided in Table 1 previous literature, [17][18][19] our findings also suggest that physicians with lower clinical FTEs had higher patient satisfaction scores, after accounting for direct and indirect associations with continuity and access to care measures. Overall, this work suggests that PCPs who choose to work fewer clinical hours may have worse continuity and access outcomes, but they may provide a better patient experience.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Definitions of the variables are provided in Table 1 previous literature, [17][18][19] our findings also suggest that physicians with lower clinical FTEs had higher patient satisfaction scores, after accounting for direct and indirect associations with continuity and access to care measures. Overall, this work suggests that PCPs who choose to work fewer clinical hours may have worse continuity and access outcomes, but they may provide a better patient experience.…”
Section: Discussionsupporting
confidence: 52%
“…16 Furthermore, the patient perspective on being cared for by a part-time PCP is not well understood. One systematic review concluded that provider work hours had no relationship with patient satisfaction, [16][17][18] yet because of the lack of welldesigned studies, the authors could not make strong conclusions about these findings. 13 However, there are several possible reasons why physicians with fewer clinical full time equivalents (FTEs) may have higher patient satisfaction scores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RVUs can be used as an objective measure of productivity, such as comparisons based on RVUs per hour [19]. RVUs can also be applied to cost analysis and to benchmarking [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…1 Previous studies identified system 25 and provider 616 characteristics that contribute to variations in care quality.…”
Section: Introductionmentioning
confidence: 99%